A Case of Hemorrhagic Dengue Encephalitis: A Rare Presentation of Dengue Expanded Syndrome (Journal of Dhaka Medical College, 2023)
Dengue encephalitis is a rare manifestation of dengue fever. Headache disorientation and or seizure gives the clinical suspicion of encephalitis in the case of dengue. Hemorrhagic encephalitis has been reported very scarce. Here we reported a case of hemorrhagic encephalitis who presented with fever, severe headache, and disorientation. MRI of the brain revealed early subacute in both temporal and frontal lobes.J Dhaka Med Coll. 2021; 30(2) : 232-236